Profile Analysis of the Scientific Articles Published in the Journal of Morphological Sciences between 2000 and 2017: A Bibliometric Study - Rueff-Barroso, Carlos Romualdo; Sepulchro, Lorraine Christiny Costa; Delpupo, Fernanda Vieira Botelho; Damm, Patrícia Breciani; Pomer-Escher, Graziela Gurtler; Camisasca, Danielle Resende; Fazan, Valéria Paula Sassoli (Journal of Morphological Sciences, 2018)
Introduction The Journal of Morphological Sciences (JMS), the official journal of the Brazilian Society of Anatomy, is an interesting option for researchers to publish in the field of morphology. It includes articles that cover a wide variety of topics, such as gross and microscopic human and animal anatomy, embryology, cell and molecular biology, clinical cases and reviews. We aimed to perform a bibliometric study to analyze the profile of JMS publications from 2000 to 2017, in order to understand in depth the origins of the researches and the subject of the manuscripts published in this journal.Material and Methods This is a descriptive bibliographical review research, with a bibliometric analysis of the scientific production of the JMS between 2000 and 2017. A total of 894 publications were analyzed, and they were distributed in 63 issues and organized into 18 volumes. Three groups of information were considered: a) “identification of the published articles;” b) “origin and authorship of the published articles;” and c) “research subject in the published articles.”Results Most of the published manuscripts were original articles (72.5%) and their subjects were mainly microscopic animal anatomy (27%) and gross human anatomy (26.6%). A total 63.3% of the manuscripts involved at least one Brazilian institution, and 59.4% of those were public institutions.Conclusion This manuscript provides an important contribution to those who are publishing in the JMS, since the authors can find a great deal of information on the quality of the science that is being published in the journal, as well as demographic information on authors and institutions.
Keywords: bibliometry; bibliometric study; scientific production; research subject; journal of morphological sciences